2020
DOI: 10.1101/2020.01.29.924100
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Potential inhibitors for 2019-nCoV coronavirus M protease from clinically approved medicines

Abstract: Starting from December 2019, a novel coronavirus, named 2019-nCoV, was found to cause Severe Acute Respiratory (SARI) symptoms and rapid pandemic in China.With the hope to identify candidate drugs for 2019-nCoV, we adopted a computational approach to screen for available commercial medicines which may function as inhibitors for the M pro of 2019-nCoV. Up to 10 commercial medicines that may form hydrogen bounds to key residues within the binding pocket of 2019-nCoV M pro were identified, which may have higher m… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
83
0
2

Year Published

2020
2020
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(85 citation statements)
references
References 13 publications
0
83
0
2
Order By: Relevance
“…Based on the structural information of clinical effective medicines for SARS-CoV-2, Liu et al predicted 10 commercial medicines which may function as inhibitors of SARS-CoV-2, including colistin, valrubicin, icatibant, bepotastine, epirubicin, etc. Some of these may be more resistant to viral mutation than lopinavir/ritonavir [133]. Stebbing et al suggested that baricitinib may reduce both the viral entry and inflammation [134].…”
Section: Treatment and Managementmentioning
confidence: 99%
“…Based on the structural information of clinical effective medicines for SARS-CoV-2, Liu et al predicted 10 commercial medicines which may function as inhibitors of SARS-CoV-2, including colistin, valrubicin, icatibant, bepotastine, epirubicin, etc. Some of these may be more resistant to viral mutation than lopinavir/ritonavir [133]. Stebbing et al suggested that baricitinib may reduce both the viral entry and inflammation [134].…”
Section: Treatment and Managementmentioning
confidence: 99%
“…The lack of success might be related to the above-mentioned plasticity of the binding cavity. Some of these compounds have been used for docking and virtual screening research aimed not only at SARS-CoV [42,43] but also at the novel SARS-CoV-2 [15][16][17][18][19][20][21]. Such an approach focuses mostly on the structural similarity between the binding pockets, but ignores the fact that the actual available binding space differs significantly.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, an in silico attempt has already been made involving a massive virtual screening for Mpro inhibitors of SARS-CoV-2 using Deep Docking [15]. Other recent attempts focused on virtual screening for putative inhibitors of the same main protease of SARS-CoV-2 based on the clinically approved drugs [16][17][18][19][20][21], and also based on the compounds from different databases or libraries [22][23][24]. However, none of such attempts is likely to lead to clinical advances in the fight against SARS-CoV-2 for reasons we elaborate below.…”
Section: Introductionmentioning
confidence: 99%
“…Ramsedivir, a broad spectrum antivirus has demonstrated in vitro and in vivo efficacy against SARS-CoV-2 and has also initiated its clinical trial [63,64]. In addition, other potential drugs from existing antiviral agent have also been proposed [65,66].…”
Section: Treatmentsmentioning
confidence: 99%